The Research of Mobile phone Entrance Guard System Model based on the Encryption Two-dimensional Code - Chu Jianli; Sun Yongdao; Liu Xia (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This article designs a new mobile-phone entrance guard system, uses the encryption two-dimensional code for identity authentication. Different from other similar products in the market, this system does not rely on specialized mobile phone card or NFC (near field communication) module. It can be directly realized through mobile-phone software, and it can be operated simple and safer. This article designs the whole system model, includes structure, function and workflow. It also analyzes and researches the main algorithms used in the system, which include security policy algorithm, encryption two-dimensional code algorithm and image recognition algorithm. Finally, it provides the solution method for the problem in the experimental simulation. It also evaluated and summarized the experimental results. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3281